2011
DOI: 10.2105/ajph.2011.300281
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Social Networks of African American Men Who Have Sex With Men Only and Those Who Have Sex With Men and Women

Abstract: Objectives We compared social network characteristics of African American men who have sex with men only (MSMO) with social network characteristics of African American men who have sex with men and women (MSMW). Methods Study participants were 234 African American men who have sex with men who completed a baseline social network assessment for a pilot behavioral HIV prevention intervention in Baltimore, Maryland, from 2006 through 2009. We surveyed the men to elicit the characteristics of their social networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 36 publications
3
37
0
Order By: Relevance
“…32 In one of the few studies to compare social and sexual networks among men who had sex with men only and men who had sex with both men and women, the authors concluded that sex partners who were not also members of participants’ emotional and economic support networks may be the best positioned to introduce and spread new ideas about condom use. 17 The authors argue, however, that these more casual and informal partnerships may not be the best positioned to establish norms of communication on risk reduction and support for HIV prevention and treatment. 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 In one of the few studies to compare social and sexual networks among men who had sex with men only and men who had sex with both men and women, the authors concluded that sex partners who were not also members of participants’ emotional and economic support networks may be the best positioned to introduce and spread new ideas about condom use. 17 The authors argue, however, that these more casual and informal partnerships may not be the best positioned to establish norms of communication on risk reduction and support for HIV prevention and treatment. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Social network characteristics including size, composition, density, norms, and communication patterns have been associated, with both HIV risk and protective behaviors across diverse populations. 1317 Among highly marginalized populations, networks may provide the only source of social and informational support. 18 In a qualitative study among male to female transgender sex workers in Boston, MA, the authors found that social networks, particularly the role of the transgender or gay mother, were crucial for helping younger transgender sex workers to navigate transactional sex encounters, given that so many were alienated from their families and faced daunting stigma, discrimination, and poverty.…”
mentioning
confidence: 99%
“…Although most studies have shown lower HIV prevalences in MSMW than MSMO [6, 1820], a growing number of studies indicate that MSMW practice more unprotected sex with their female than with their male partners [6, 10, 11, 18, 19, 21]. These studies include one showing a higher likelihood of serodiscordant unprotected sex with female than with male partners in Black MWMW who are HIV-positive [19].…”
Section: Introductionmentioning
confidence: 99%
“…. Studies incorporating HIV testing have reported rates as high as 30-50% among black MSMW (Latkin et al, 2011;Tieu et al, 2012). Black MSMW may also be more likely than MSM of other race/ethnicities to have undiagnosed infection (Maulsby, Sifakis, German, Flynn, & Holtgrave, 2012;Young, Shoptaw, 5 It is likely that sexual behaviors differ between male, female, and transgender partners of MSMW .…”
mentioning
confidence: 99%